Identification of Megaselia scalaris (Diptera : Phoridae) based on morphology and mitochondrial 16S rRNA and COI gene sequences (Dhaka University Journal of Biological Sciences, 2016)
Megaselia scalaris (Diptera: Phoridae), commonly known as scuttle fly, is widely distributed all over the world. It is easily cultured in the laboratory condition making it a potential model organism. Besides, it has forensic importance. However, no report from Bangladesh could be retrieved about this fly. So, in the present study, identification of this species was attempted using both morphological and molecular approaches. Characteristics of male hypopygium and legs played key roles in morphological identification. To strengthen identification, mitochondrial COI and 16S rRNA gene fragments were amplified and sequenced. Blast search at NCBI provided highest hits to available COI and 16S rRNA sequences of M. scalaris. A neighbor joining phylogenetic tree was built using sequences of respective COI gene region to show its relationship among other closely related dipteran flies.Dhaka Univ. J. Biol. Sci. 25(2): 149-159, 2016 (July)